2017
DOI: 10.3906/sag-1503-163
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxidative stress in α-amanitin-induced hepatotoxicityin an experimental mouse model

Abstract: Background/aim: This study aimed to evaluate oxidative stress markers of liver tissue in a mouse α-amanitin poisoning model with three different toxin levels. Materials and methods:The mice were randomly divided into Group 1 (control), Group 2 (0.2 mg/kg), Group 3 (0.6 mg/kg), and Group 4 (1.0 mg/kg). The toxin was injected intraperitoneally and 48 h of follow-up was performed before sacrifice.Results: Median superoxide dismutase activities of liver tissue in Groups 3 and 4 were significantly higher than in Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Therefore, this 2 µM dose was particularly relevant for testing the efficacy of an antidote on these two parameters. These results are in line with the literature data on the involvement of oxidative stress in amanitin toxicity (DüNdar et al, 2017;Zheleva, 2013;Zheleva et al, 2007). Our study showed that differentiated HepaRG cells constitute a sensitive, reproducible model for studying the toxicity of amanitin.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, this 2 µM dose was particularly relevant for testing the efficacy of an antidote on these two parameters. These results are in line with the literature data on the involvement of oxidative stress in amanitin toxicity (DüNdar et al, 2017;Zheleva, 2013;Zheleva et al, 2007). Our study showed that differentiated HepaRG cells constitute a sensitive, reproducible model for studying the toxicity of amanitin.…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, Wang et al (2018) showed that αamanitin induces significant changes in the mitochondrial proteome and might destroy the mitochondrial membrane potential (Wang et al, 2018). It has also been suggested that oxidative stress is important in the development of severe hepatotoxicity, since α-amanitin accumulation leads to an increase in the activity of superoxide dismutase (SOD) and glutathione peroxidase, the production of malondialdehyde, and lipid peroxidation, and inhibits catalase activity (DüNdar et al, 2017;Zheleva et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The generation of oxidative stress has also been suggested to be important in the development of these severe hepatotoxicities. Indeed, it has been shown that α-amanitin accumulation leads to an increase in superoxide dismutase (SOD) and glutathione peroxidase activity, malondialdehyde products, and lipid peroxidation, correlated with an inhibition of catalase activity [25,26]. Recently, new mechanistic data have shown that amanitins induce the production of GSH and tGSH, reinforcing the hypothesis of the involvement of oxidative stress in this pathophysiology [18].…”
Section: Toxicity Of Amanitins: From Clinical To Molecular Mechanismsmentioning
confidence: 87%
“…The inhibition of RNA polymerase II is considered to be the main mechanism of toxicity, leading to the inhibition of protein synthesis and subsequent liver toxicity [7]. Other mechanisms, such as the formation of reactive oxygen species, caspase-3dependent apoptosis, and the upregulation of tumor necrosis factor-α, may be involved as well [1,5,6,9,10]. In patients, Amanita phalloides poisonings start with a latency phase followed by a gastrointestinal phase 12-24 h after the ingestion of the mushrooms [4,11].…”
Section: Introductionmentioning
confidence: 99%